The Yanakuna indigenous community’s own food. A resistance strategy - Perafán Chilito, Wilder (Facultad de Ciencias Políticas y Sociales, 2021)
Food is part of a body of knowledge rooted in culture, the possession of seeds, the place where indigenous can cultivate and the ways to prepare land. This work characterizes the food system of the Yanakuna indigenous community located in the south of the department of Huila, divided into six settlements, with approximately two thousand indigenous people. A qualitative ethnographic research was used, accompanied by a proprietary methodology based on “Cultivation, breeding and sowing of wisdom and knowledge (ccrissac, for its translation in Spanish)”. The research showed they still cultivate and preserve traditional recipes that allow them to maintain a good nutrition, it is also necessary to expand the lands of the reservation to implement traditional crops.